Postoperative red blood cell transfusion and morbid outcome in uncomplicated cardiac surgery patients - Möhnle, Patrick; Snyder-Ramos, Stephanie; Miao, Yinghui; Kulier, Alexander; Böttiger, Bernd W.; Levin, Jack; Mangano, Dennis T. (Intensive care medicine, 2011)
To evaluate postoperative red blood cell (RBC) transfusion and its association with postoperative cardiac events and multiorgan morbidity in uncomplicated cardiac surgery patients.